Re-designing nano-silver technology exploiting one-pot hydroxyethyl cellulose-driven green synthesis - Blosi, M.; Brigliadori, A.; Ortelli, S.; Zanoni, I.; Gardini, D.; Vineis, C.; Varesano, A.; Ballarin, B.; Perucca, M.; Costa, A. L. (Frontiers in Chemistry, 2024)
Re-designing existing nano-silver technologies to optimize efficacy and sustainability has a tangible impact on preventing infections and limiting the spread of pathogenic microorganisms. Advancements in manufacturing processes could lead to more cost-effective and scalable production methods, making nano-silver-based antimicrobial products more accessible in various applications, such as medical devices, textiles, and water purification systems. In this paper, we present a new, versatile, and eco-friendly one-pot process for preparing silver nanoparticles (AgNPs) at room temperature by using a quaternary ammonium salt of hydroxyethyl cellulose (HEC), a green ingredient, acting as a capping and reducing agent. The resulting nano-hybrid phase, AgHEC, consists of AgNPs embedded into a hydrogel matrix with a tunable viscosity depending on the conversion grade, from ions to nanoparticles, and on the pH. To investigate the synthesis kinetics, we monitored the reaction progress within the first 24 h by analyzing the obtained NPs in terms of particle size (dynamic light scattering (DLS), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM)), Z-potential (ELS), surface plasmon resonance (UV-VIS), crystallographic phase (XRD), viscosity, and reaction yield (inductively coupled plasma-optical emission spectrometry (ICP-OES)). To explore the design space associated with AgHEC synthesis, we prepared a set of sample variants by changing two independent key parameters that affect nucleation and growth steps, thereby impacting the physicochemical properties and the investigated antimicrobial activity. One of the identified design alternatives pointed out an improved antimicrobial activity in the suspension, which was confirmed after application as a coating on nonwoven cellulose fabrics. This enhancement was attributed to a lower particle size distribution and a positive synergistic effect with the HEC matrix.